2014
DOI: 10.1007/s00442-014-3069-5
|View full text |Cite
|
Sign up to set email alerts
|

Prey perception of predation risk: volatile chemical cues mediate non-consumptive effects of a predator on a herbivorous insect

Abstract: Predators can affect prey in two ways-by reducing their density (consumptive effects) or by changing their behavior, physiology or other phenotypic traits (non-consumptive effects). Understanding the cues and sensory modalities prey use to detect predators is critical for predicting the strength of non-consumptive effects and the outcome of predator-prey encounters. While predator-associated cues have been well studied in aquatic systems, less is known about how terrestrial prey, particularly insect larvae, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 51 publications
4
82
1
Order By: Relevance
“…Prey organisms rely on visual, chemical, and mechanical cues from predators and, as a general rule from behavioral studies, the stronger and riskier the cue detected, the stronger the resulting antipredator response (Relyea 2003). In this issue, Hermann and Thaler (2014) show that a terrestrial beetle uses olfactory cues and other information to detect predators and that the olfactory cues differ for male and female predators. Interestingly, beetles find male predators "smellier" than females even though females are more lethal, potentially creating a disjunct between information and actual risk.…”
Section: Features Of the Special Issuementioning
confidence: 98%
“…Prey organisms rely on visual, chemical, and mechanical cues from predators and, as a general rule from behavioral studies, the stronger and riskier the cue detected, the stronger the resulting antipredator response (Relyea 2003). In this issue, Hermann and Thaler (2014) show that a terrestrial beetle uses olfactory cues and other information to detect predators and that the olfactory cues differ for male and female predators. Interestingly, beetles find male predators "smellier" than females even though females are more lethal, potentially creating a disjunct between information and actual risk.…”
Section: Features Of the Special Issuementioning
confidence: 98%
“…The prey may respond to the presence of predators using different types of cues, for example tactile, chemical and visual cues (Rypstra & Buddle, ; Hermann & Thaler, ). Volatile chemicals produced by ants, for example have previously been shown to affect movement behaviour of spiders (Mestre, Bucher & Entling, ).…”
Section: Discussionmentioning
confidence: 97%
“…Ants are known to behave aggressively, and insects they attack either try to escape (run, fly away or drop off plants) or adopt defensive behaviour, for example retract body parts and press their body to the surface (Messina, ; Völkl, ; Majerus et al ., ). In addition to physical contact, recent research has shown that reductions in insect herbivory can be mediated through non‐consumptive effects induced by several other kinds of cues from predators, for example visual or chemical (Rypstra & Buddle, ; Hermann & Thaler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Prey may respond to predation threat with immediate behavioral changes such as reduction in activity or feeding to become less conspicuous to predators (Bernays , Hermann and Thaler ), or with physiological changes such as altered development or growth (Hawlena et al , Thaler et al ). For example, Manduca sexta larvae alter behavior (feeding rate) and physiology (assimilation efficiency and glycogen levels) in response to predation risk.…”
Section: Predicted Outcomes Of Arthropod Non‐consumptive Effects (Ncementioning
confidence: 99%